The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/ett.3188
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly behavior analysis for IoT sensors

Abstract: The Internet of Things (IoT) will not only connect computers and mobile devices but also interconnect smart buildings, homes, and cities, as well as electrical grids, gas, and water networks, automobiles, airplanes, etc. IoT will lead to the development of a wide range of advanced information services that need to be processed in real time and require large storage and computational power. The integration of IoT with fog and cloud computing not only brings the computational requirements but also enables IoT se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…The issues of security and privacy in fog and mobile edge computing are also a concern that many researchers are considering in their work. The authors of related works have briefly presented these issues and considered some counter measurements. A selective forwarding model that provides monitoring capabilities for detecting malicious nodes and tracing nodes' movements has been presented in the work of Yaseen et al The model has shown huge improvements in terms of detecting malicious nodes by leveraging the fog computing infrastructure.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The issues of security and privacy in fog and mobile edge computing are also a concern that many researchers are considering in their work. The authors of related works have briefly presented these issues and considered some counter measurements. A selective forwarding model that provides monitoring capabilities for detecting malicious nodes and tracing nodes' movements has been presented in the work of Yaseen et al The model has shown huge improvements in terms of detecting malicious nodes by leveraging the fog computing infrastructure.…”
Section: Related Workmentioning
confidence: 99%
“…Integration of IoT devices with fog computing has enabled richer IoT services that are cost effective and allow for accessibility from anywhere at any time . However, there are some major security challenges that need to be considered.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A crucial challenge in proposing a new edge computing solution is to realistically assess the performance of the envisioned system while considering the relevant engineering parameters. The researchers can use the real cloud environments, experimental test beds, or simulators to evaluate their approaches. There are pros and cons in selection of these options.…”
Section: Introductionmentioning
confidence: 99%
“…One critical requirement in enabling efficient CRIoT networking with time‐critical traffic is operating under the unavailability security threat . In CRIoT networks, the unavailability threat is defined by the denial of a CRIoT device from successfully delivering data packets within a given delay requirements by disrupting/jamming the communications over the selected channel(s) .…”
Section: Introductionmentioning
confidence: 99%